Ukuran Perusahaan, Kecukupan Modal, Risiko, Dan Stabilitas Keuangan Bank Syariah Di Indonesia - Chandra Budi Oktavionita; Siti Nur Azizah; Iwan Fakhruddin; Hardiyanto Wibowo (Universitas Muhammadiyah Malang, 2022)
This study aims to examine the effect of firm size, capital adequacy, financing risk, and firm stability on profitability based on stakeholder and agency theory. This research is a quantitative study on Islamic banking companies in Indonesia in 2017-2020 with a purpose sampling technique of 14 Islamic Commercial Banks (BUS) registered with the Financial Services Authority. Analyzed using panel data regression. The results of this study indicate that firm size and capital adequacy have a positive effect. Meanwhile, financing risk and stability did not show any effect on profitability. This empirical study contributes to the theory and practice of companies. These findings can also be a reference for the government as a policy maker.